Meningkatkan Keterampilan Sosial Anak melalui Metode Roleplay dan Modeling di Komunitas Harapan Pasar Johar - Lulus Anggun Listiyani; Sischa Wahyuwardhani; Angky Melani; Novi Widya Sari; Siti Hikmah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The Komunitas Harapan in Kauman Village, Semarang, was established to address social issues among children, including the lack of social skills due to the influence of a harsh environment. This study aims to evaluate the effectiveness of role-playing and modeling methods in improving the social skills of children in the community. The method used is a quantitative approach with an action research model, involving 11 child subjects ranging from kindergarten to elementary school age. Data were collected through observations, interviews, and pre-tests and post-tests. The analysis results show an increase in social skills that is not statistically significant, with a difference of 11.82 points between the average pre-test and post-test scores. However, qualitative observations reveal a positive impact, including increased responsiveness to instructions and mastery of basic social skills such as apologizing. In conclusion, although the quantitative results were not significant, this intervention has a positive impact on the development of children's social skills, which requires more time and a deeper approach for optimal results